EKSISTENSI PRODUK PERBANKAN SYARIAH PADA KOPERASI SERBA USAHA AL- KAHFI JOMBANG - Azizah, Ninik; Laras Sati, Dewi (Irtifaq, 2021)
Cooperatives are non-bank financial institutions that have an important role in developing the economy of a country, multi-business cooperatives try to play their role in accordance with the law stipulated in Law Number 17 of 2012 concerning Cooperatives. With a qualitative approach to this type of field research, data from observations, interviews and documentation are analyzed deductively by taking theories, or the rules of sharia business ethics related to the existence of sharia products in KSU, then the theory is drawn to the reality or facts of cases in the field. The results show that Islamic banking products should not be applied in KSU but because of the existence of regulations, the KSU can apply these sharia products which are exempted from Law No. 5/1999 concerning the Prohibition of Monopolistic Practices and Business Competition in article 50. Meanwhile In increasing customers, KSU Al-Kahfi applies several superior products, namely promo deposits, and there are several other products. Keywords; Banking Products, Multipurpose Cooperatives, Laws